Evaluasi User Experience pada Game Marvel Super War menggunakan metode Enhanced Cognitive Walkthrough - Muhammad Nicco Gumaisa; Satrio Hadi Wijoyo; Diah Priharsari (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Marvel Super War is a game released by NetEase Games, chategorized as MOBA (Multiplayer Online Battle Arena). It collaborates with Marvel Entertainment. Marvel Super War is similiar to other MOBA games such as Arena of Valor and Mobile Legends. User experience is essential for the succesful market, mainly a new released game. Systems that aren't well designed and not easy to use will leave a user difficulty to learn and operate. It will create those systems infrequently used. In order to gain a great user experience, It's required an evaluation. Enhanced Cognitive Walkthrough is a user experience evaluation method that evaluators give a task based on scenario and some questions to the users to find out the problems which trouble the learning process. This method is compatible with a new released system. It is able to identify the users' cognitive process when running the system for the first time. The respondents used in this study were divided into two groups, 3 respondents who have never played the MARVEL SUPER WAR game, 3 experienced users in playing the MARVEL SUPER WAR game and and frequently play games with similar genre. The evaluation results on the MARVEL SUPER WAR game show that many problems occur due to the lack explanations of the function (hidden) on the learning control menu. However, the problems that arise are minor problems and do not affect the main functions in the game.